A study on concept of P- drug selection among rural general practitioners - G., Priyadarshini Bai; P., Ravi Kumar (International Journal of Basic & Clinical Pharmacology, 2016)
Background: The objective of the study was to assess the awareness of P- drug selection among rural general practitioners’s (GP) for common medical conditions. Methods: Fifty general practitioners in Tumakuru district were provided with proformas for selection of P- drugs for mild to moderate hypertension, diabetes, upper respiratory tract infections and acid peptic disease based on safety, affordability, need, and efficacy (SANE criteria). Results: Forty one GP’s responded by completing the proformas. Seventeen of them were aware of the concept of P- drug selection. In hypertension, beta blockers followed by Angiotensin Converting Enzyme (ACE) inhibitors were most commonly preferred. In diabetes, biguanides followed by sulfonylureas were preferred as oral hypoglycemic agents. Ampicillin, Ciprofloxacin and Cotrimoxazole were the commonly used antibiotics for upper respiratory tract infections. Ranitidine and antacids were preferred for acid peptic disease. Affordability followed by efficacy was the deciding criteria for P- drug selection. Conclusions: There is lack of awareness of P- drug selection among many rural GP’s. Therefore, there is necessity to create awareness about P- drug selection through continued medical education for rational use of drugs.